Hugo [videorecording (Blu-Ray)] - Selznick, Brian; Butterfield, Asa, 1997-; Moretz, Chloë, 1997-; Lee, Christopher, 1922-2015 (Arrow Video, 2023)
Hugo Cabret is an orphan, living secretly in the walls of a Paris train station, tending to the many clocks, stealing what he needs to survive and hiding from the ruthless station inspector. But his clandestine life and precious secrets are threatened when he is caught thieving by the bitter old man who runs a toy booth at the station, and Hugo's world becomes enmeshed with that of the shop owner and his bookish granddaughter. A cryptic drawing, a treasured notebook, a mechanical man, and a hidden message from Hugo's dead father are all connected to a place where dreams are made.